Assessing The Relative Importance Of Competitive Priorities That Influence Consumers’ Choices In Mobile Phone Services - Tahir, Md.Nor Hayati; Mohd Sam, Mohd Fazli; Said, Mazidah; Kamarudin, Mohd Fauzi (Canadian Center of Science and Education, 2015)
-